Development of unstable resistance to diminazene aceturate in Babesia bovis - Bumduuren Tuvshintulga; Thillaiampalam Sivakumar; Naoaki Yokoyama; Ikuo Igarashi (International Journal for Parasitology: Drugs and Drug Resistance, 2019)
Diminazene aceturate (DA) is commonly used in the treatment of bovine babesiosis caused by Babesia bovis. In this study, we attempted to develop resistance in B. bovis in vitro to DA and clofazimine (CF, a novel antibabesial agent) using short- and long-term drug pressures. In the short term, we found that 6.7 ± 2 (0.54 ± 0.16 μM)-, 12.9 ± 8.6 (1.05 ± 0.7 μM)-, and 14 ± 5.9 (1.14 ± 0.48 μM)-fold increases in the half-maximal inhibitory concentration (IC50) of DA were demonstrated on B. bovis cultivated with 0.04 μM of DA pressure for 4, 8, and 12 days, respectively, as compared to that on parental culture (0.08 ± 0.0065 μM) before drug pressure was initiated. However, in B. bovis cultivated with 0.04 μM of DA pressure after 16 days, the parasites could not tolerate 0.8 μM of DA. In the long term, 7.6 ± 3.5-, 20.5 ± 0.1-, and 26.8 ± 5.5-fold increases in the IC50 of DA were demonstrated on parasites from subcultures at days 8, 3, and 5 post-cultivation, respectively, in a drug-free medium, where these subcultures were obtained from B. bovis cultivated with DA pressure with changing doses for 30, 60, and 90 days, respectively. However, the second and third times, no increase was demonstrated on B. bovis from these subcultures at days 15 and 30 post-cultivation in a drug-free medium. In addition, in B. bovis cultivated with drug pressure after 90 days, the parasites tolerate up to 0.64 μM DA. All findings demonstrated that DA resistance in B. bovis is unstable and lost within 15 days of drug withdrawal. However, treatment with subtherapeutic doses of DA in cattle might result in the development of resistance in B. bovis, which may not even respond to subsequent treatments with high doses of DA. Thus, if the bovine babesiosis caused by B. bovis is unresponsive to DA, treatment with other antibabesial agents might be recommended. Keywords: Babesia bovis, Unstable drug resistance, Diminazene aceturate, In vitro